(3eLehYI JQGLe YdeGA GdbQf GdKGdK YTQ GdgLQis - (3YGQa MceJ Hf Pj GdabGQ Hf fGaP GdgQScj,J (B1321 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI GdTjN CMeO Hf eMeO GdYOhi GdeGdci GdTgjQ HGdOQOjQ s
(3BNQgG (B:s
(3jfJgi HJQLeI jhSa GdcQOi GdMfai , GdeJhai ai MOhO SfI (B1210 (3g` s
(3JYJHQ gPg GdfSNI eShOI Chdi ddcJGH aajgG aQGZGJ cKjQIs
(3hHYV GdJQGLe de jPcQ ajgG EdG CSeGA CUMGHgGs
(3hHBNQ GdfSNI agQS ddeJQLejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B245s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B367 s
Keywords: (3GdJGQjNs